GB virus C/Hepatitis G virus infection is frequent in American children and young adults. - Handa, A; Jubran, R; Dickstein, B; Boylan, A; Luban, N; Young, N; Brown, K (2000)
The novel flavivirus GB virus C/hepatitis G virus (GBV-C/HGV) has been detected in approximately 2% of blood donors in the United States, and neutralizing antibody to the envelope protein (E2), a marker of previous infection with GBV-C/HGV, is present in approximately 9% of donors. The rate of GBV-C/HGV infection among American children is unknown. To determine whether viral infection might occur during childhood, 160 serum specimens (obtained from blood bank samples) from children and young adults with no history of transfusion were tested. Viral RNA and antibody to E2 were detected in 6.3% and 9.4% of subjects, respectively. Evidence of previous or current infection (viremia and/or antibody to E2) was detected in 13.8% of subjects, indicating that GBV-C/HGV infection appears to be common among American children and young adults, even in the absence of blood transfusion.